Near-room-temperature magnetocaloric properties of Fe75–xMnxAl25 alloys - Sharma, Vinay (2020)
Magnetic cooling systems near room temperature have attracted attention as an attractive, “green,” thermal management technology, offering high energy efficiency and environmental friendliness. There is an urgent need for low-cost, easy-to-manufacture magnetocaloric materials for such applications. We report the magnetocaloric properties of low-cost, high-relative-cooling-power (RCP) Fe 75-x Mn x Al 25 (12.5 ≤ x ≤ 25) alloys with tunable Curie temperatures. A second-order magnetic phase transition, with negligible magnetic and thermal hysteresis, was observed. Fe 60 Mn 15 Al 25 and Fe 57.5 Mn 17.5 Al 25 buttons exhibited high values of RCP, i.e., 395 and 430 J - kg -1 , respectively, and Curie temperatures near room temperature. Universal scaling behavior and local exponent analyses of the thermodynamic data were performed. The low cost, easy availability, and established manufacturing technology are additional advantages of these alloys.